SUATU TINJAUAN PELAKSANAAN PERKAWINAN DIBAWAH USIA MINIMUM DI KECAMATAN SAMARINDA ULU - Helviana Helviana (Universitas 17 Agustus 1945 Samarinda, 2013)
abstract Seeing the development of today's society, it turns out many experienced marital problems, this can be understandable, given the marriage here is an act committed by a man, while the man himself is a creature that is dynamic, with the condition that always changes according to the level of development. As one of the problems that often arise in the conduct of a marriage is about determining the age limit for marriage could hold, Determination of the age limit to hold the marriage is important, because marriage as a covenant between a man's engagement with a woman as husband and wife.